Esensi Kohesivitas untuk Mendukung Performa Olahraga Beregu - Andreas J. F. Lumba; Christin P. M. Rajagukguk (Jurnal Muara Olahraga, 2021)
Maximum performance and positive trends have always been the goal of every coach entrusted to coach a sports team, but these expectations have not been appropriately realized. The stagnation of team sports achievement in East Nusa Tenggara Province needs to find a solution to improve it. Psychology is one of the fields of study that can improve the stagnation of achievement in team sports. There are many positive consequences of increasing cohesiveness in team sports. The positive consequences of cohesiveness in sports have been described in the various scientific literature; for example, cohesiveness training affects performance, cohesiveness, and collective success contribute to team performance, and cohesiveness can build teams. Cohesiveness and anxiety are important factors for athlete performance. Thus, in team sports, cohesiveness greatly contributes to improving athlete performance.